2013
DOI: 10.1038/modpathol.2012.207
|View full text |Cite
|
Sign up to set email alerts
|

Determination of primary versus secondary membranous glomerulopathy utilizing phospholipase A2 receptor staining in renal biopsies

Abstract: Autoantibody formation directed against phospholipase A2 receptor (PLA2R)1 is the underlying etiology in most cases of primary membranous glomerulopathy. This new understanding of the pathogenesis of primary membranous is in the process of transforming the way the disease is diagnosed. We validated an indirect immunofluorescence assay to examine PLA2R1 in renal biopsies utilizing a commercially available antibody and standard indirect immunofluorescence. Using this assay, we examined a total of 165 cases of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
195
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(212 citation statements)
references
References 25 publications
11
195
1
5
Order By: Relevance
“…High titers are correlated to low risk of spontaneous remission and higher risk of the emergence of nephrotic syndrome in non‐nephrotic patients. Diagnostic sensitivity of anti‐PLA2R antibodies was found to be 70.6%, and diagnostic specificity of anti‐PLA2R antibody vs normal and pathological controls was 100% and 94.6%, respectively, as per Radice et al7 In 2013, examining 165 biopsies of primary and secondary membranous, Larsen et al8 reported sensitivity of 75% and a specificity of 83% for primary membranous glomerulopathy on PLA2R staining. Other causes of positive PLA2R biopsy staining were found to have hepatitis C, sarcoidosis (75%), and neoplasm (25%).…”
Section: Discussionmentioning
confidence: 78%
“…High titers are correlated to low risk of spontaneous remission and higher risk of the emergence of nephrotic syndrome in non‐nephrotic patients. Diagnostic sensitivity of anti‐PLA2R antibodies was found to be 70.6%, and diagnostic specificity of anti‐PLA2R antibody vs normal and pathological controls was 100% and 94.6%, respectively, as per Radice et al7 In 2013, examining 165 biopsies of primary and secondary membranous, Larsen et al8 reported sensitivity of 75% and a specificity of 83% for primary membranous glomerulopathy on PLA2R staining. Other causes of positive PLA2R biopsy staining were found to have hepatitis C, sarcoidosis (75%), and neoplasm (25%).…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, the sensitivity and specificity of this testing for primary MN remain to be defined across all populations. The original report by Beck et al (4) suggested a sensitivity of approximately 75% and a specificity of 100% using a serologic assay; however, subsequent reports have suggested a higher sensitivity combining serum and biopsy testing for anti-PLA 2 R antibodies (11), whereas other studies have reported a low rate of detection of anti-PLA 2 R antibodies in patients with MN with comorbidities typically associated with secondary forms of the disease, including hepatitis C, sarcoidosis, malignancy, and lupus (5,14). Therefore, the most conservative approach is to interpret a positive anti-PLA 2 R antibody test (whether by serum or biopsy staining) as highly consistent with primary MN; conversely, a negative anti-PLA 2 R antibody test denotes either a secondary form of MN or the roughly 20%-25% of primary patients who associate with a different autoantibody.…”
Section: Discussion Of Question 1bmentioning
confidence: 94%
“…In addition, patients with MN related to sarcoidosis or active hepatitis B may show an increased prevalence of anti-PLA2R antibodies, which suggests that immunological disorders associated with these two diseases might induce or enhance immune response against PLA2R [48,49].…”
Section: Anti-pla2r Antibodiesmentioning
confidence: 99%